Interactive Mobile Learning: Developing and Evaluating an Android-Based Monopoly Game for Enhancing Engagement and Learning Outcomes in Elementary School (IJORER : International Journal of Recent Educational Research, 2026)
Objective: To address the persistent challenges of low engagement and poor outcomes in elementary social studies instruction. This study aimed to develop an Android-based Monopoly game and examine its effects on fourth-grade students’ engagement and learning outcomes regarding Indonesian Cultural Diversity. Method: A Research and Development approach was integrated with a quasi-experimental nonequivalent control group pretest–posttest design involving 62 fourth-grade students (experimental: n = 32; control: n = 30) from two public elementary schools in Central Java. Data collected through validated engagement questionnaires and cognitive achievement tests were analyzed using one-way ANCOVA (with pretest as covariate), independent samples t-tests, N-gain, and Cohen’s d. Results: Expert validations confirmed the media’s feasibility as ‘Very Feasible’ (88.02%, ICC = 0.882). ANCOVA results demonstrated that the experimental group achieved significantly higher posttest scores than the control group after controlling for pretest scores (F(1, 59) = 6.12, p = 0.016, η²p = 0.094), supported by a larger N-gain (0.38 vs. 0.29) and a medium effect size (d = 0.58). Furthermore, experimental students reported meaningfully higher behavioral, emotional, and cognitive engagement (d = 0.65). Novelty: This study provides empirical evidence on the synergistic potential of combining gamification mechanics with mobile platforms for culturally specific content. It demonstrates how interactive game-based pedagogy can successfully operationalize the student-centered principles of the Kurikulum Merdeka framework, specifically addressing the lack of technology-enhanced media in the integrated IPAS (Ilmu Pengetahuan Alam dan Sosial) curriculum.